PERANCANGAN TATA KELOLA TEKNOLOGI INFORMASI DENGAN MENGGUNAKAN FRAMEWORK COBIT 2019 PADA PT JWT GLOBAL LOGISTICS INDONESIA - Augustine Archi Mariatama; Lovinta Happy Atrinawati; Muhammad Gilvy Langgawan Putra (Program Studi Sistem Informasi, Universitas Banten Jaya, 2022)
PT JWT Global Logistics Indonesia is company in logistic field (cargo services, freight forwarding, export and import). Utilization of information technology in this company has not fully played a role in achieving company goals. Therefore, the design of information technology governance using COBIT 2019 framework to overcome these problems. This research starts from literature study and reach out the problem at PT JWT Global Logistics Indonesia. The next step is using COBIT 2019 framework that is understand the enterprise context and strategy, determine the initial scope of the governance system, refine the scope of the governance system, and conclude the governance system design which results in governance design in the form of value for 40 core models. COBIT 2019 measures each core model with design factor toolkit. Each design factor contains a statement that is tailored to the enterprise’s condition. Core model which has target of capability level of 4 is APO03 Managed Enterprise Architecture, APO12 Managed Risk, BAI06 Managed IT Changes and DSS01 Managed Operations.